Empowering Women Evidence from a Field Experiment in Afghanistan - Beath, Andrew (The World Bank, 2012)
In societies with widespread gender discrimination, development programs that encourage female participation in local governance can potentially redress gender imbalances in economic, political, and social outcomes. Using a randomized field experiment encompassing 500 Afghan villages, this study finds that a development program which incorporates mandated female participation increases female mobility and involvement in income generation, but does not change female roles in family decision-making or attitudes toward the general role of women in society